Strengthening Students' Religious Character through REMAS Organizations: Synergistic School Culture and Education Strategies - Nur Dwi Kurnianti Anti; Syamsul Arifin (Managere: Indonesian Journal of Educational Management, 2025)
This study aims to analyze the synergistic strategies between Islamic Religious Education (PAI) teachers and school culture in shaping students’ religious character through the Remaja Masjid (Remas) organization. The research is grounded in the challenges of globalization and modernization that continue to erode students’ spiritual values, requiring a contextual and collaborative approach to character development. Using a qualitative case study design, data were collected through in-depth interviews and participatory observation of religious activities including istighosah, Qur’anic recitation, fiqh discussions, and social service. The findings show that the effectiveness of Remas as a medium for religious character formation relies heavily on the strategic involvement of PAI teachers as facilitators, mentors, and spiritual role models, combined with active student participation in managing the programs. Additionally, a supportive school culture, including leadership support, cross-subject teacher engagement, and adequate facilities, strengthens the internalization of Islamic values across the school environment. The study concludes that Remas, when supported by aligned educational strategies and a positive organizational culture, becomes more than an extracurricular activity. It represents a comprehensive model for integrated and sustainable religious character education that can be adapted by other educational institutions.